2018
DOI: 10.1038/s41598-018-34509-1
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology reveals the unique mechanism features of Shenzhu Capsule for treatment of ulcerative colitis in comparison with synthetic drugs

Abstract: In clinic, both synthetic drugs and Shenzhu Capsule (SZC), one kind of traditional Chinese medicines (TCMs), are used to treat ulcerative colitis (UC). In our study, a systems pharmacology approach was employed to elucidate the chemical and mechanism differences between SZC and synthetic drugs in treating UC. First, the compound databases were constructed for SZC and synthetic drugs. Then, the targets of SZC were predicted with on-line tools and validated using molecular docking method. Finally, chemical space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 72 publications
(77 reference statements)
0
30
0
Order By: Relevance
“…Increasing evidence showed that the traditional Chinese medicines can be applied to treat UC [4]. Feng et al [5] indicated that Shenzhu Capsule contained two herbal medicines (Renshen and Baizhu) and improved UC by altering TNF signalling pathway, Toll-like receptor signalling pathway and NF-kb signalling pathway. Qingchang Wenzhong Decoction comprising of eight kinds of herbs attenuated dextran sulphate sodium-(DSS-) induced UC in rats by upregulating macrophage-stimulating protein concentration/receptor tyrosine kinase signalling pathway [6].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence showed that the traditional Chinese medicines can be applied to treat UC [4]. Feng et al [5] indicated that Shenzhu Capsule contained two herbal medicines (Renshen and Baizhu) and improved UC by altering TNF signalling pathway, Toll-like receptor signalling pathway and NF-kb signalling pathway. Qingchang Wenzhong Decoction comprising of eight kinds of herbs attenuated dextran sulphate sodium-(DSS-) induced UC in rats by upregulating macrophage-stimulating protein concentration/receptor tyrosine kinase signalling pathway [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SZC could reversely regulate the expression of some genes (metabolic, ion channels and transport proteins) in SGC-7901 tumor-bearing mice, resulting in the improvement of gastric cancer through multiple targets [22]. Moreover, SZC not only regulated immune and inflammatory responses during the treatment of ulcerative colitis (UC), but also acted on UC complications (bloody diarrhea) and prevented UC from developing into colorectal cancer [23]. At present, our attentions are being paid to investigate whether SZC exhibits therapeutic effect on CID, the GI side effect of chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…proteins identied in the network based on the interaction between active ingredients and target proteins. 81 As shown in Fig. 7 and 8, molecular docking analysis showed that hydrogen bonds can form spontaneously between the 7 core compounds and the target proteins.…”
Section: Discussionmentioning
confidence: 96%